Kegiatan Story Telling Dalam Meningkatkan Kemampuan Speaking Anak - Noerjanah, Noerjanah; Khomarun, Khomarun (Universitas Pahlawan Tuanku Tambusai, 2024)
Language is a tool to improve communication skills for society. English is one of the languages that needs to be developed in elementary school children, where this age is a good start for learning the language. This community service aims to introduce simple English speaking practices to elementary school children in grades 5 and 6 at TPA Majid Baitul Basyiir using the Speaking skill practice approach which is related to some colors. This activity was carried out for 6 months from July 2024 to Desember 2024 with the form of activities in the form of providing training to elementary school children in grades 5 and 6 at the Baitul Basyiir Mosque TPA, visits to villages/groups and direct practice with children in Tohudan Village, Colomadu District, Karanganyar Regency. Keywords: children, story telling, speaking